2013
DOI: 10.1021/ie403045y
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Molecular Architecture As a Tool for Controlling the Rheological Properties of Aqueous Polyacrylamide Solutions for Enhanced Oil Recovery

Abstract: The controlled synthesis of high molecular weight branched polyacrylamide (PAM) has been accomplished by using atomic transfer radical polymerization (ATRP) of acrylamide (AM) in water at room temperature. Halogen-functionalized aliphatic polyketones acted as macroinitiators in the polymerization. The obtained branched polymers were used in water solutions to study the effect of the molecular architecture on the rheological properties. For comparison purposes, linear PAM was synthesized by using the same proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 61 publications
3
51
0
2
Order By: Relevance
“…These researchers concluded that the arms of the star polymer stretch to best accommodate both intra-and interarm repulsions. Wever et al 16 also report that the arms adapt a more stretched conformation with an increase in number of arms in a star polymer. The increased free volume of the LMA-MMA 50 star polymer relative to its copolymer analogue apparently has a more dominant effect on the phase behavior than the MMA−propane energetic mismatch that is magnified with the large number of MMA groups within the star polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…These researchers concluded that the arms of the star polymer stretch to best accommodate both intra-and interarm repulsions. Wever et al 16 also report that the arms adapt a more stretched conformation with an increase in number of arms in a star polymer. The increased free volume of the LMA-MMA 50 star polymer relative to its copolymer analogue apparently has a more dominant effect on the phase behavior than the MMA−propane energetic mismatch that is magnified with the large number of MMA groups within the star polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…According to Perrier [40], the past years of research have now allowed RAFT to become a tool in which new complex and functional materials can be made. A relevant example, although at laboratory scale, is the synthesis of polyacrylamide with a well-defined branched structure for applications in chemical enhanced oil recovery, as developed within our Groningen University Product Technology group by Wever [44] and more recently by v. Mastrigt [45]. Other recent examples illustrate the possibility of using photo-initiated RAFT polymerization in emulsion, further expanding its scope [46,47].…”
Section: Future Prospects Of Crp-methods In Industrial Settingsmentioning
confidence: 99%
“…Для продвижения по пласту используют растворы полимеров, высокая вязкость ко-торых позволяет применять оторочки ми-целлярными растворами меньших объе-мов. Хорошая смесимость мицеллярных растворов с водой и нефтью, а также дос-таточно низкое поверхностное натяжение на границе раздела создают благоприятные условия для вытеснения нефти [14,15].…”
Section: мероприятия по совершенствованию разработкиunclassified
“…Рассмотрены возможности приме-нения полимерного заводнения, закачки мицеллярных растворов и теплоносителя. Потокоотклоняющие технологии и поли-мерное заводнение будут наиболее эффек-тивны для данной залежи с высоковязкой нефтью [15][16][17].…”
Section: заключениеunclassified